Pulse length effects on autoionizing states under the influence of intense SASE XUV fields. (9th November 2020) - Aufleger, L; Friebel, P; Rupprecht, P; Magunia, A; Ding, T; Rebholz, M; Hartmann, M; Stooß, V; Ott, C; Pfeifer, T
Abstract: The Fano absorption line shape of an autoionizing state encodes information on its internal atomic structure and dynamics. When driven near-resonantly with intense extreme ultraviolet (XUV) electric fields, the absorption profile can be deliberately modified, including observable changes of both the line-shape asymmetry and strength of the resonance, revealing information on the underlying dynamics of the system in response to such external driving. We report on the influence of the XUV pulse parameters at high intensity that can be achieved with a free-electron laser (FEL) with statistically broadened spectra based on self-amplified spontaneous emission (SASE). More specifically, the impact of the FEL pulse duration is studied for the example of the doubly excited 2s2p resonance in helium, where line-shape modifications have been measured with XUV transient absorption spectroscopy in Fraunhofer-type transmission geometry. A computational few-level-model provides insight into the impact of different average pulse durations of the stochastic FEL pulses. These findings are supported by measurements performed at the Free-Electron Laser in Hamburg (FLASH) and provide further insight into XUV strong-coupling dynamics of resonant transitions driven by intense high-frequency FEL sources.